Capaian Aspek Kompetensi Sains Siswa SMA dengan Pembelajaran Model Problem-Based Learning dan Cooperative Learning Tipe STAD - Trisna Amelia; Nevrita Nevrita; Desi Rahmatina (Magister Pendidikan Biologi, Universitas Negeri Medan, 2020)
Science literacy is an essential element of science and technology learning. The mastery of science literacy drives people being competitive and worth employed, especially in the workplace where an employee is expected to be innovative. Globally the mastery of society's science literacy of Indonesian students was still low. Science literacy consists of 4 dimensions, namely context, science competence, knowledge, and science attitude. The science competency dimension becomes important to be achieved by the students as an indicator of the achievement of science literacy. Related to improving science literacy through components of learning strategy, based on various relevant research, in SMA Negeri 1 Tanjungpinang has been conducted a study to compare the achievement of science competency with Problem-based learning and Cooperative Learning (STAD type). To test whether there is a significant difference in the average level of science competency scores between the PBL class and the CL-STAD class in SMA 1 used Mann-Whitney test which shows a significant value of 0.000 < 0.05. These results show that there is a significant difference in the average level of science competency of the students X IPA class with the implementation of the PBL and CL-STAD in SMA 1 Tanjungpinang. The achievement of science competency in PBL class is higher than the achievement in CL-STAD class based on 3 aspects, namely: identifying scientific issues, explaining scientific phenomena, and using scientific evidence.